Multiplex serology for Streptobacillus moniliformis and other ‘rat bite fever-like’ microorganisms for seroprevalence studies in rodents - Katja Schmidt; Julia Butt; Ulrich Matt; Klaus Vogel; Calvin Mehl; Rainer G. Ulrich; Tobias Eisenberg (PLoS ONE, 2025)
Rat bite fever (RBF) is a zoonotic disease caused primarily by Streptobacillus (S.) moniliformis. Norway or brown rats (Rattus [R.] norvegicus) are the natural host for S. moniliformis and carry the bacterium in the nasopharynx without clinical disease. Transmission to humans often occurs through rat bites or scratches, but also through contact with the excreta of infected rats. Although human infections with S. moniliformis occur worldwide, they are rarely diagnosed. For decades, S. moniliformis was the only known member of the genus Streptobacillus. In recent years, however, four additional species were identified, two of which being zoonotic pathogens capable of causing symptoms identical to RBF in humans. The aim of this study was to develop a serological assay covering all known Streptobacillus species. A bead-based multiplex fluorescence immunoassay for S. moniliformis detection has been used for years in routine diagnostics of laboratory rodents. Here, this assay was adapted to enable the detection of antibodies against all currently known Streptobacillus species and tested with sera from experimentally inoculated mice and rats, and with negative sera from laboratory rodents. Using this assay, we broadly examined the prevalence of Streptobacillus spp. reactive antibodies in wild rodents. Transudates from a total of 107 Norway rats, 81 black or roof rats (Rattus rattus) and 110 house mice (Mus musculus) from different husbandries and wildlife populations within Germany were tested. Antibody prevalences of 41% in R. norvegicus and 83% in R. rattus suggest that Streptobacillus spp. are widespread in wild and captive rats in Germany, whereas wild mice seem to be free of infection. Due to its high throughput capacity and multiplex format, the Streptobacillus multiplex serology is well suited for large seroprevalence studies in rodents and has the potential, after adaptation, for use in humans, thereby allowing for the assessment of Streptobacillus infection risk and risk of RBF.